2020
DOI: 10.5812/numonthly.107859
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Liver Enzymes in End-Stage Renal Disease Patients on the Renal Transplant-Waiting List in North-West of Iran

Abstract: Background: Liver diseases, mainly hepatitis B and C, commonly occur in patients with end-stage renal diseases (ESRD). Alanine and aspartate aminotransferase are important for the diagnosis and monitoring of liver diseases. Several studies demonstrated that patients with chronic kidney disease (CKD) have lower levels of serum aminotransferases than the normal population. The present study was designed to compare these enzymes in different types of dialysis in ESRD patients and the general population in Iran. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This is shown in Table 7. In the previous studies, patients having dialysis for the long time were found to have transaminases level in the serum close to the normal ranges 8 . Transaminases levels were found to be reduced in pre-dialysis patients of chronic kidney disease, the level of AST was investigated 9 .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This is shown in Table 7. In the previous studies, patients having dialysis for the long time were found to have transaminases level in the serum close to the normal ranges 8 . Transaminases levels were found to be reduced in pre-dialysis patients of chronic kidney disease, the level of AST was investigated 9 .…”
Section: Resultsmentioning
confidence: 91%
“…In case of chronic kidney disease, uremic toxins increases in the blood. This causes decreased production of transaminases from the hepatocytes 8,9 . GGT resulted in being independent foretelling indicator of cardiovascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…Other possibilities included decreased synthesis and inhibition of release of AST and ALT from hepatocytes or accelerated clearance from serum. [13][14][15][16] A low serum aminotransferase level could also be due to water retention and hemodilution in patients of CKD. 10 However, this pattern is usually not maintained in CKD with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] Other possibilities included decreased synthesis and inhibition of release of AST and ALT from hepatocytes or accelerated clearance from serum. [ 12 13 14 15 16 ] A low serum amino-transferase level could also be due to water retention and hemodilution in patients of CKD. [ 10 ] However, this pattern is usually not maintained in CKD with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] and Sabouri et al . [ 16 ] have emphasized that the use of standard reference values for amino-transferases to help detect liver disease, is less useful in CKD patients, and have proposed that separate normal (lower) reference ranges of serum aminotransferases in different stages of CKD need to be determined. However, in stark contrast to their findings there is a paradigm shift with respect to serum ALT/AST levels in SARS-CoV-2 afflicted CKD patients, who show elevations from baseline levels that lie beyond normal conventional laboratory ranges.…”
Section: Discussionmentioning
confidence: 99%